Construct validity examination of inquisitiveness indicator on critical thinking disposition test in biology - J Syahfitri; H Firman; S Redjeki; S Sriyati (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Inquisitiveness is one of indicators of the critical thinking disposition which is curiosity to gain knowledge. The aims of this research were to examine the construct validity of inquisitiveness indicators on critical thinking disposition test in biology. The critical thinking disposition test consisted of 22 multiple choice questions that have been validated by experts and the items were presented through cases relating to biological content. This research involved 526 students of biology education from University of Muhammadiyah Bengkulu and the State University of Bengkulu in the grade of study (year 1, year 2, year 3, and year 4). Based on the confirmation by confirmatory factor analysis, this research found that the critical thinking disposition test for inquisitiveness indicators had the suitable construct validity for 10 items. This results were supported with the acceptable values of convergent validity, they were the standardized factor loading more than 0.5, composite reliability 0.57 and average variance extract 0.93. from those results of this research, it can concluded that this instrument has a high validity and reliability to measure inquisitiveness of critical thinking disposition in biology.